2008
DOI: 10.1111/j.1537-2995.2008.01711.x
|View full text |Cite
|
Sign up to set email alerts
|

Dispermic chimerism identified during HLA typing for stem cell transplantation

Abstract: This case represents dispermic chimerism, with one maternal and two paternal haplotypes variably distributed throughout body tissues in a phenotypically normal man without abnormalities in blood typing. The presence of additional alleles that may have been undetected or dismissed by serologic typing should be carefully investigated and verified by molecular techniques. Molecular HLA typing may increase the accurate identification of phenotypically normal chimeras and aid in selecting proper donors for transpla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Chimerism is suspected when individuals have abnormalities in blood typing results, ambiguous genitalia, or abnormal karyotypes . True chimeras have varying degrees of cell duality in different body tissues . Chimerism can be divided into partial hematopoietic chimerism and whole‐body chimerism.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Chimerism is suspected when individuals have abnormalities in blood typing results, ambiguous genitalia, or abnormal karyotypes . True chimeras have varying degrees of cell duality in different body tissues . Chimerism can be divided into partial hematopoietic chimerism and whole‐body chimerism.…”
Section: Introductionmentioning
confidence: 99%
“…Chimerism can be divided into partial hematopoietic chimerism and whole‐body chimerism. Several mechanisms for the development of whole‐body chimerism have been suggested including postzygotic fusion of 2 embryos (tetragametic chimerism), postzygotic diploidization of a triploid zygote and fertilization of a parthogenetic oocyte or an oocyte and its polar body by 2 sperm . Partial chimerism can be observed in dizygotic twins where hematopoietic cells have been exchanged in a context of twin‐twin transfusion over vascular anastomoses between 1 dichorionic placentas.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chimerism, a state described as the presence of two genetically distinct cell lines in an organism, routinely occurs in patients who have been subjected to medical procedures such as transplantation or transfusion (Starzl & Demetris, 1998;Kruskall et al, 2001). A few cases of phenotypically normal dispermic chimeras have been reported in literature (Watkins et al, 1981;Schoenle et al, 1983;Tsuji et al, 1996;Malan et al, 2006;Mosebach et al, 2006;Draper et al, 2008). Almost all of these cases showed abnormalities on blood typing (Mifsud et al, 1999;Lo et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…A retrospective, multicenter study of 63 children (aged 0.2-17 years) showed that allogeneic hematopoietic stem cell transplantation was able to rescue a significant proportion of children with acute myeloid leukemia in second complete remission -especially if a human leukocyte antigen-compatible relative is a donor [41]. In a case representing dispermic chimerism in a 32-year-old man diagnosed with acute myelomonocytic leukemia, Draper et al [42] showed that molecular human leukocyte antigen typing is required to reduce transplant rejection in such patients. Majhail et al [43] demonstrated that human leukocyte antigen mismatched umbilical cord blood is an alternative graft source for elderly who need a transplant but do not have a matched related donor.…”
Section: Leukemia: a Cancer Of Bone Marrow And Lymphocytesmentioning
confidence: 99%